The Philippines in Imperial History: Reynaldo Clemeña Ileto, Pasyon and Revolution: Popular Movements in the Philippines, 1840-1910. Manila: Ateneo de Manila University Press, 1979; 1997. Issue 4 (4th July 2021) - Hopkins, A. G.
ABSTRACT: The aim of this article is to draw the attention of historians of empire to one of the most neglected components of Western imperial systems. Although the Philippines was ruled successively by Spain, the United States, and Japan for more than four centuries, it occupies only minor place in standard histories of Western imperialism and often is not mentioned at all. Yet, historians of the Philippines have produced work of high standard on themes that prompt comparison with studies of other colonies. The illustrations selected here refer, respectively, to the rise of anti-colonial movements within the colony and the links between embryonic nationalism and similar trends elsewhere in Southeast and East Asia. The originality and vitality of the literature on the Philippines deserves to be much better known outside the country. Equally, historians of the Philippines can gain from connecting their work to the wider historiography of Western imperialism.